Georgia : Fourth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Economic growth continues to be strong, but inflation has increased substantially. The structural agenda remains focused on further improving tax and customs administration, improving fiscal planning and public expenditure management, and strengthening financial markets. The main risks to the economic outlook stems from domestic and external political pressures. Despite these risks and the recent surge in inflation, the government's strong track record and the commitment to take corrective measures, as needed, bode well for the successful implementation of the program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet